Augmented Reality in STEM Education: Enhancing Conceptual Understanding and Learner Motivation - Ardi Azhar Nampira; Sanjay Sharma; Dorji Wangchuk (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid development of digital technologies has encouraged the integration of augmented reality (AR) in STEM education as a response to persistent challenges in conceptual understanding and learner motivation. Purpose. This study aims to examine the effectiveness of augmented reality in enhancing students’ conceptual understanding and learning motivation in STEM subjects. Method. The research employed a quasi-experimental design with a mixed-methods approach, involving experimental and control groups at the secondary and tertiary education levels. Quantitative data were collected through pre-test and post-test instruments measuring conceptual understanding and standardized motivation questionnaires, while qualitative data were obtained from observations and semi-structured interviews. Results. The findings indicate that students exposed to AR-based learning environments demonstrated significantly higher gains in conceptual understanding compared to those taught using conventional methods. Additionally, AR integration positively influenced learner motivation, particularly in terms of attention, relevance, and engagement during learning activities. Conclusion. The study concludes that augmented reality is an effective pedagogical tool for STEM education, as it supports deeper conceptual learning and fosters intrinsic motivation.